THE PROCESS OF GENERATING VIBROACOUSTIC SIGNALS DURING CUTTING - Mirzayev, Murodil (Educational Research in Universal Sciences, 2022)
This article provides information on the analysis of the process of generating vibroacoustic signals during cutting.